SPUF design based on Camellia encryption algorithm. (June 2021) - Chen, Jia; Wang, Pengjun; Zhang, Yuejun; Zhang, Huihong
Abstract: To meet the security requirements of resource-constrained systems, a software PUF (SPUF) scheme based on the encryption algorithm is proposed using the timing violation to generate the chip's fingerprint. In this work, the Camellia encryption algorithm is selected and implemented via a semi-custom design flow to get the deviation of circuit delay. And then, the delay time of critical path of the proposed circuit is generated through static timing analysis. Using the overclocking frequency, the Camellia encryption algorithm circuit operates at timing violation status. We can collect the wrong response data of the simulation result at different input signals. The wrong data caused by timing violation can be defined as output of SPUF, which is the chip's fingerprint. To improve the randomness, the multi-round operation of the Camellia is used to process the SPUF data. The experimental results show that the uniqueness of SPUF is 50.01%, the SPUF data passes the NIST test, and no additional hardware overhead is required.